Antimicrobial Effect of Different Sizes of Nano Zinc Oxide on Oral Microorganisms - Fatemeh Mirhosseini; Motahareh Amiri; Alireza Daneshkazemi; Hengameh Zandi; Zoleikha Sadat Javadi (Tehran University of Medical Sciences, 2019)
Objectives: The purpose of the present study was to evaluate the antimicrobial effect of various sizes and concentrations of zinc oxide (ZnO) nanoparticles on Streptococcus mutans (SM), Enterococcus faecalis (EF), Lactobacillus fermentum (LF), and Candida albicans (CA). Materials and Methods: Solutions at the concentration of 10 µg/ml were prepared using 20-nm, 40-nm, and 140-nm nano ZnO (nZnO) powder. The antimicrobial effect of nZnO was determined using the disk diffusion method. The inhibition zone (mm) was measured using a ruler. Data were analyzed by analysis of variance (ANOVA) and the Bonferroni correction. The minimum inhibitory concentrations (MICs) and minimum bactericidal concentrations (MBCs) of nZnO were determined using the broth microdilution method in Mueller-Hinton Agar (MHA) for SM and EF, De Man, Rogosa, and Sharpe (MRS) agar, and Sabouraud Dextrose Agar (SDA). Results: The greatest inhibition zones were observed against SM with 20-nm and 40-nm nZnO, while 140-nm nZnO formed the greatest inhibition zones against SM and EF. The smallest inhibition zones were observed against CA with the three nZnO particle sizes. The MICs for CA with 40-nm and 140-nm particles and for LF with 140-nm particles were higher than 10 µg/ml. A significant correlation was found between the particle size and the antibacterial activity against SM (P=0.00), LF, and EF (P<0.02). Conclusions: The antimicrobial activity of nZnO increases with decreasing the particle size. The greatest antimicrobial effect was observed against SM and EF. SM is more sensitive to the changes in the particle size compared to other bacteria.